Resistance against two lytic phage variants attenuates virulence and antibiotic resistance in Pseudomonas aeruginosa - García-Cruz, Juan Carlos; Rebollar-Juarez, Xareni; Limones-Martinez, Aldo; Santos-Lopez, Cristian Sadalis; Toya, Shotaro; Maeda, Toshinari; Ceapă, Corina Diana; Blasco, Lucia; Tomás, María; Díaz-Velásquez, Clara Estela; Vaca-Paniagua, Felipe; Díaz-Guerrero, Miguel; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Background Bacteriophage therapy is becoming part of mainstream Western medicine since antibiotics of clinical use tend to fail. It involves applying lytic bacteriophages that self-replicate and induce cell lysis, thus killing their hosts. Nevertheless, bacterial killing promotes the selection of resistant clones which sometimes may exhibit a decrease in bacterial virulence or antibiotic resistance. Methods In this work, we studied the Pseudomonas aeruginosa lytic phage φDCL-PA6 and its variant φDCL-PA6α. Additionally, we characterized and evaluated the production of virulence factors and the virulence in a Galleria mellonella model of resistant mutants against each phage for PA14 and two clinical strains. Results Phage φDCL-PA6α differs from the original by only two amino acids: one in the baseplate wedge subunit and another in the tail fiber protein. According to genomic data and cross-resistance experiments, these changes may promote the change of the phage receptor from the O-antigen to the core lipopolysaccharide. Interestingly, the host range of the two phages differs as determined against the Pseudomonas aeruginosa reference strains PA14 and PAO1 and against nine multidrug-resistant isolates from ventilator associated pneumonia. Conclusions We show as well that phage resistance impacts virulence factor production. Specifically, phage resistance led to decreased biofilm formation, swarming, and type III secretion; therefore, the virulence towards Galleria mellonella was dramatically attenuated. Furthermore, antibiotic resistance decreased for one clinical strain. Our study highlights important potential advantages of phage therapy’s evolutionary impact that may be exploited to generate robust therapy schemes.